THE EFFECT OF CHEMOTHERAPY ON BLOOD CELL COUNTS IN POST-MASTECTOMY BREAST CANCER PATIENTS - Muhammad Haerunnizam; Pancawati Ariami; Thomas Tandi Manu; Lale Budi Kusuma Dewi (Meditory : The Journal of Medical Laboratory, 2025)
Background: Post-mastectomy chemotherapy often causes myelosuppression, as do the numbers of erythrocytes, leukocytes, and platelets.Objective: To determine the effect of chemotherapy on the number of blood cells in post-mastectomy breast cancer patients.Methods: This study was a retrospective observational study. The population in the study was breast cancer patients who underwent chemotherapy  0 (Pre-chemotherapy) to 4 times after mastectomy at the NTB Provincial Hospital from January to December 2024. Sampling was done using non-probability sampling with a purposive sampling method, resulting in 68 samples.Results: In the study, the average number of erythrocytes from session 0 (Pre-chemotherapy) to session 4 was 4,23; 3,80; 3,67; 3,59, and 3,6 million cells/µL. Then, the average number of leukocytes from session 0 (Pre-chemotherapy) to session 4 was 7,208; 5,024; 4,739; 3,690, and 3,281 thousand cells/µL. Meanwhile, the average number of platelets from session 0 (Pre-chemotherapy) to session 4 was 386,251; 302,792; 275,760; 228,014, and 206,035 thousand cells/µL. Based on the Friedman test data analysis, the results showed a significance value of 0.001 < 0.05.Conclusions: There is an effect of chemotherapy on the number of blood cells in post-mastectomy breast cancer patients.